2017
DOI: 10.1534/g3.116.035873
|View full text |Cite
|
Sign up to set email alerts
|

First in Vivo Batrachochytrium dendrobatidis Transcriptomes Reveal Mechanisms of Host Exploitation, Host-Specific Gene Expression, and Expressed Genotype Shifts

Abstract: For generalist pathogens, host species represent distinct selective environments, providing unique challenges for resource acquisition and defense from host immunity, potentially resulting in host-dependent differences in pathogen fitness. Gene expression modulation should be advantageous, responding optimally to a given host and mitigating the costs of generalism. Batrachochytrium dendrobatidis (Bd), a fungal pathogen of amphibians, shows variability in pathogenicity among isolates, and within-strain virulenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 62 publications
6
32
0
Order By: Relevance
“…Newts exposed to the P20 isolate had greater odds of dying from Bsal chytridiomycosis compared to the P200 isolate, indicating differences in pathogenicity caused by passage history. Several studies on the genetically similar Bd chytrid fungus have reported loss of pathogen virulence associated with greater number of passages in culture [16,17,27]. Increased passage number can reduce zoospore production rate and total number of zoospores produced by zoosporangia [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Newts exposed to the P20 isolate had greater odds of dying from Bsal chytridiomycosis compared to the P200 isolate, indicating differences in pathogenicity caused by passage history. Several studies on the genetically similar Bd chytrid fungus have reported loss of pathogen virulence associated with greater number of passages in culture [16,17,27]. Increased passage number can reduce zoospore production rate and total number of zoospores produced by zoosporangia [27].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced selection (i.e., attenuation) or differential expression of virulence genes in culture could have influenced pathogenicity [17], as suggested by studies comparing Bd that was recently isolated from wild hosts to Bd in cell culture. For example, Ellison et al [16]found that Bd transcriptomes isolated from two infected amphibian hosts exhibited higher expression of genes associated with increased virulence when compared to a Bd culture grown in the lab. Rosenblum et al [28] also reported that Bd cultured on frog skin displayed a greater number of genes coding for proteases that affect pathogenicity when compared to Bd cultured using tryptone media [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of datasets with higher percentages of pathogen reads was conducted to show when and how patterns changed across the range of the percentages of pathogen reads. Some systems investigate simultaneous gene expression of host and pathogens by mechanically separating cells of each species prior to sequencing (Ellison, DiRenzo, McDonald, Lips, & Zamudio, ). Datasets with higher percentages of pathogen reads that still include host reads could represent sequencing from RNA extracted after imperfect cell sorting.…”
Section: Methodsmentioning
confidence: 99%
“…For example, when grown in vivo in a susceptible species versus in culture, the fungus ( B. dendrobatidis) simultaneously increased expression of transcripts involved in proteolysis, transmembrane transport and cilium morphogenesis, and exhibited a shift in expressed genotype frequencies (Ellison et al . ). Disentangling the extent to which host genomic and transcriptomic variation may influence rapid evolution in parasite populations holds great promise for refining our understanding of disease dynamics.…”
Section: Genomicsmentioning
confidence: 97%